Dalen & Gole. Scandal in Port Angus - Deas, Mike, 1982- (Orca Book Publishers, 2011)
Dalen and Gole, two aliens from planet Budap, discover a strange tunnel that leads them to Port Angus, Earth, a small fishing community that is slowly dying. Once there, the two discover an alien plot to steal Port Angus' fish in order to power their technology on Budap.